Perancangan Alat Pencegah Kerumunan Otomatis di Masa COVID-19 Berbasis RFID (Radio Frequency Identification) - Agus Juhana (Jurnal Sistem Cerdas, 2021)
AKB (New Habit Adaptation) requires people, especially in Indonesia to carry out their usual activities by complying with health protocols during the COVID-19 pandemic. The government continues to develop new policies to protect its citizens, including urging the public to avoid crowds wherever they are, including in-office areas. The purpose of this research is to make a system design that can monitor the gathering activities of office employees according to government regulations, namely not filling a room with more than 50% of the maximum capacity of the room. The result of this research is a design of hardware and software as an interface device that can automatically count the number of people in a room with the help of an RFID (Radio-frequency identification) sensor. Besides, this system design is also able to store data of employees who are active in a room and detect their temperature, if the room's capacity is full, the door will automatically be locked and will not accept other employees to enter the room. The hope is that this design can help office management to always supervise points of office space that are often filled with employees so that it also helps the government so that people always avoid crowds.